2020
DOI: 10.17509/jpki.v6i1.23179
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Dukungan Keluarga dan Teman Sebaya terhadap Ibu Menyusui Neonatus di Rumah Sakit: Telaah Literatur

Abstract: ABSTRAKPemberian ASI pada neonatus di rumah sakit mengalami banyak tantangan. Sementara itu, mempertahankan pemberian ASI dapat meningkatkan status kesehatan bayi, menurunkan morbiditas dan mortalitas neonatal. Intervensi untuk mempertahankan menyusui selama masa perawatan diantaranya dukungan menyusui dari keluarga dan teman sebaya. Tujuan penulisan artikel adalah untuk menelaah pengaruh intervensi dukungan keluarga dan teman sebaya terhadap ibu menyusui neonatus di rumah sakit. Artikel ini menggunakan pendek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Research in Depok, West Java by (Natalia & Rustina, 2020) also states that mothers who get good support from grandmothers and other families will have the opportunity to provide exclusive breastfeeding 3.7 times better than mothers whose grandmother's social support is lacking. The support of a grandmother who firmly thinks that breastfeeding is the best will make it easier for mothers to give exclusive breastfeeding to their babies (Natalia & Rustina, 2020). The role of grandmothers and their families is proven to be significant in the success of providing breastfeeding practices and increasing the rate of exclusive breastfeeding.…”
Section: Resultsmentioning
confidence: 99%
“…Research in Depok, West Java by (Natalia & Rustina, 2020) also states that mothers who get good support from grandmothers and other families will have the opportunity to provide exclusive breastfeeding 3.7 times better than mothers whose grandmother's social support is lacking. The support of a grandmother who firmly thinks that breastfeeding is the best will make it easier for mothers to give exclusive breastfeeding to their babies (Natalia & Rustina, 2020). The role of grandmothers and their families is proven to be significant in the success of providing breastfeeding practices and increasing the rate of exclusive breastfeeding.…”
Section: Resultsmentioning
confidence: 99%
“…It also found that most postpartum mothers experience moderate anxiety with the first and second children, and postpartum mothers' anxiety is often associated with their job. Housewives are pressured by working on multiple tasks at home and becoming role models for their children (Dibaji et al, 2017), and the support from family can help a postpartum mother (Natalia & Rustina, 2020).…”
Section: Discussionmentioning
confidence: 99%